2023
DOI: 10.1186/s12866-023-02861-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, antibiofilm, and anti-quorum sensing activities of pyocyanin against methicillin-resistant Staphylococcus aureus: in vitro and in vivo study

Abstract: Background Methicillin-resistant Staphylococcus aureus (MRSA) infections are considered a major public health problem, as the treatment options are restricted. Biofilm formation and the quorum sensing (QS) system play a pivotal role in S. aureus pathogenicity. Hence, this study was performed to explore the antibacterial effect of pyocyanin (PCN) on MRSA as well as its effect on MRSA biofilm and QS. Results Data revealed that PCN exhibited strong an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Biofilm infections are extremely difficult to treat with common antibiotics, resulting in chronic infections and non-healing wounds. As a result, it has been necessary to develop new antibacterial agents that are effective against biofilm [ 38 ]. For instance, New biofilm-inhibiting substances are urgently needed to combat refractory infections like methicillin-resistant S. aureus (MRSA) and vancomycin-methicillin-resistant S. aureus because biofilms play crucial roles in antibiotic resistance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm infections are extremely difficult to treat with common antibiotics, resulting in chronic infections and non-healing wounds. As a result, it has been necessary to develop new antibacterial agents that are effective against biofilm [ 38 ]. For instance, New biofilm-inhibiting substances are urgently needed to combat refractory infections like methicillin-resistant S. aureus (MRSA) and vancomycin-methicillin-resistant S. aureus because biofilms play crucial roles in antibiotic resistance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 ), the APLss effect in downregulating virulence gene expressions was apparent. Notably, agrA expression was found to be significantly downregulated in both MSSA and MRSA strains; this parameter was linked to quorum sensing, and quorum sensing has been shown to positively influence biofilm formation and virulence attributes like hla production [ 56 59 ]. Results from animal models and human cases of serious necrotizing illnesses caused by group A streptococcus and clostridial species have demonstrated that toxin suppression improves outcomes [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that Pseudomonas aeruginosa itself remains resistant to the antibacterial properties of pyocyanin (Özyürek et al 2016 ). Experimental results published by Kamer et al ( 2023 ) further demonstrated the ability of pyocyanin to exhibit antimicrobial activity against methicillin‐resistant Staphylococcus aureus (MRSA) strains that were highly unsusceptible to most antibiotics including oxacillin, cefoxitin, penicillin, gentamycin, and erythromycin. This is highly significant since MRSA is a major causative agent in hospital-acquired diseases and has been associated with prolonged infection and increased mortality (Lakhundi and Zhang 2018 ).…”
Section: Biomedical Applications Of Pyocyaninmentioning
confidence: 99%
“…Pyocyanin was able to inhibit all the aforementioned strains with an MIC of merely 38.05 μM. It was also able to significantly eradicate the biofilm formed by these MRSA strains in a concentration-dependent manner, destroying 29.7–56.8% of the biofilm at 47.56 μM with its anti-biofilm action increasing to 69–79.4% at 95.13 μM and finally, 83–88% at 190.26 μM (Kamer et al 2023 ). While the currently available results are highly promising for the use of pyocyanin as an antibacterial, further research is necessary to ascertain the effect of pyocyanin on various beneficial bacteria such as Lactobacillus sp.…”
Section: Biomedical Applications Of Pyocyaninmentioning
confidence: 99%